Ethical Witnessing, Home, and Return in Ghassan Kanafani’s Returning to Haifa: A Decolonial and Religious Humanities Reading - Dadang Ismatullah; Sri Rijati Wardiani; Titin Nurhayati Ma'mun; Sangidu Sangidu (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
Palestinian exile in Ghassan Kanafani’s fiction deeply reshapes the relationships connecting individuals to home, memory, and historical existence. While existing scholarship has largely emphasized political nationalism, trauma, and structural settler-colonial violence, the ethical dimensions and processes of cultural sacralization sustained within disrupted domestic spaces remain underexplored, particularly in relation to how secular resistance narratives resonate within religious readerships. This article examines how home, memory, and return are represented in Returning to Haifa through an integrated framework of settler-colonial studies and the religious humanities. Employing qualitative textual analysis and close reading of both the Arabic original and its English translation, the study focuses on narrative structure, spatial description, and intergenerational dialogue. The analysis shows that home functions not merely as a domestic setting but as a culturally sacralized space where moral attachments endure against colonial erasure. Memory emerges as a form of ethical witnessing, while the transformation of Khaldun into Dov exposes the intimate violence of intergenerational rupture. This study contributes to religious literary studies by demonstrating how Kanafani’s secular narrative undergoes religious re-signification within contemporary Muslim horizons of expectation, demonstrating how such a moral reframing is enacted by specific communities of reading through shared ethical imaginaries of dignity (al-karamah) and historical continuity.